Pengaruh Hipnoterapi dan Akupresur terhadap Mual Muntah Akut Akibat Kemoterapi Pada Anak dengan Acute Lymphoblastic Leukemia (ALL) di Rumah Sakit Umum Kabupaten Tangerang Tahun 2017 - Restu Iriani; Evi Vestabilivy (Jurnal Persada Husada Indonesia, 2017)
The effect of chemotherapy cause pain and side effect, such as nausea and vomiting will cause discomfort. One of the intervention to reduce nausea and vomiting with complementary therapies is hypnotherapy and accupressure. The purpose of this study was to determine the effect of hypnotherapy and accupressur on acute nausea and vomiting caused chemotherapy in children with ALL. This studies is a quasy experimental with non equivalent without control group design. This studies was conducted in Anyelir room of general hospital Tangerang district on 27 children with purposive sampling, consisting of three treatment group each 9 respondent. The collected of data uses the Rhodes INVR questionnaire. The result showed significant effect of accupressure (p value= 0,003), hypnotherapy (p value= 0,000), hypnotherapy and accupressure (p value= 0,015) to reduce nausea and vomiting caused chemotherapy in ALL children. Accupresure and hypnotherapy can reduce acute nausea and vomiting caused by chemotherapy in school children with ALL so it is recommended that this study be applicable as a complementary therapy.